Molecular characterization and potential therapeutic roles of miR125a in HER-2 positive gastric cancer - Afraa Mamoori; Zena Hasan Sahib; Haider Alkafaji (Indian Journal of Pathology and Microbiology)
Introduction: miR-125a-3p could have a role in gastric cancer by targeting HER2. This study aimed to investigate the expression pattern of miR-125a-3p, identify the expression level of its target gene in gastric carcinoma, and test its effect in HER-2 positive gastric carcinoma cells. Materials and Methods: The levels of miR-125a-3p in both cancer and noncancer tissues were measured by using Quantitative real-time polymerase chain in 70 gastric carcinomas. Immunohistochemical study was used to measure the expression of HER2 protein in these carcinomas. In addition, the level of expression of this miRNA is correlated to different pathological and clinical parameters. The effects of miR-125a-3p alone and in combination with 5-FU (fluorouracil) on the growth of HER2 positive (NUGC4) and HER2 negative (ECC10) gastric carcinoma cells were also analyzed by in vitro studies. Results: Most gastric cancer tissues samples showed downregulation of miR-125a-3p (84%) when compared to their noncancer tissues. Significant correlations of downregulation of miR-125a-3p with cancer recurrence and pathological staging of gastric carcinoma (P = 0. 02 and 0.02, respectively) were noted. HER2 protein expression correlated significantly and inversely with miR-125a-3p expression (P < 0.05). A reduction in cell growth rate was noted significantly in miR-125a-3p transfected gastric carcinoma cells when 5-FU was added to them in comparison to other control cells (P < 0.01). When both gastric carcinoma cell lines were transfected with miR-125a-3p, a significantly higher growth inhibition percentage in HER2 positive (NUGC4) cell line was seen in comparison to the HER2 negative (ECC10) cells (P < 0.01). Conclusion: miR-125a-3p plays a significant role in the pathogenesis of gastric carcinoma. Therapeutic transfection of miR-125a-3p in HER2 positive gastric cancer cells resulted in reduced cell proliferation and potentiate the effect of 5-FU.